(untitled) (Journal of Biochemistry, Microbiology and Biotechnology, 2024)
Butterfly pea flower, also known as Asian pigeon wings, has been widely used as an ingredient in food and medicine due to the high content of various types of antioxidants that are beneficial to health. One of the technologies used to extract the bioactive compound from the plant is the ultrasound-assisted extraction (UAE) method. This study aimed to investigate the effect of different extraction times from 10 min to 30 min and types of solvent: water, aqueous methanol and aqueous ethanol on the phenolic compound and antioxidant activity present in the butterfly pea flower. The total phenolic content (TPC) was determined using Folin-Ciocalteu assay while the antioxidant was assessed using 2,2-diphenyl-1-picrylhydrazyl (DPPH) scavenging assay. Based on this study, the optimal condition to increase the extract yield from butterfly pea flower was found to be at a 20-min sonication, while the highest TPC and antioxidant activity were achieved at a 30-min sonication using aqueous methanol. Compared with maceration, UAE demonstrated better results in percentage yield, TPC and antioxidant activity when using aqueous methanol. This approach indicated that UAE is an efficient technique for obtaining bioactive compounds from butterfly pea flowers.